Relative income and its relationship with mental health in UK employees: A systematic review - Bethany Croak; Laura E. Grover; Simon Wessely; Kalpa Kharicha; Danielle Lamb; Sharon A.M. Stevelink (PLoS ONE, 2025)
Purpose: The relative income hypothesis theorises that one’s earnings relative to others exert a greater influence on subjective wellbeing than absolute income. Understanding the relationship between relative income and mental health could contribute to employee wellbeing. This review aimed to summarise the defining features of relative income in relation to mental health and how it is measured in the literature. In addition, it aimed to explore the relationship between relative income and mental health in those currently employed in the UK. Methods: Nine electronic databases were searched using a pre-defined search strategy: PubMed (including MEDLINE and PubMed Central), PsycINFO, Scopus, Web of Science, Global Health, JSTOR, Business Source Complete (EBSCO), ScienceDirect and Emerald. The protocol was pre-registered on PROSPERO (CRD42023408657). Quantitative and qualitative studies and grey literature, which described the defining features and measurement of relative income and its impact on mental health among UK employees, were included. Results: After screening, 13 studies were included in the review. A conceptualisation of relative income revealed that an income comparison is either researcher-defined using averages or self-assessed based on a person’s perception. Having a lower income than the reference group was commonly associated with diminished wellbeing, though moderating factors (gender, income inequality and composition of reference group) were identified. Conclusions: Having a lower income than the reference group is associated with poorer wellbeing. Implications for practice and policy are considered amidst the UK’s ‘cost of living crisis’ and ongoing pay disputes in various sectors.